1993
DOI: 10.1128/mcb.13.5.3084
|View full text |Cite
|
Sign up to set email alerts
|

The ADP/ATP carrier is the 32-kilodalton receptor for an NH2-terminally myristylated src peptide but not for pp60src polypeptide.

Abstract: Membrane binding of pp60src is initiated via its myristylated NH2 terminus. To identify a candidate pp6G' docking protein or receptor in the membrane, a radiolabelled peptide corresponding to the pp6tO' NH2-terminal membrane binding domain was cross-linked to fibroblast membranes and found to specifically label a 32-kDa protein. This protein was purified by appending an affinity tag to the peptide probe so that the cross-linked complex could be isolated via affinity chromatography. Microsequencing indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 24 publications
(56 reference statements)
3
9
0
Order By: Relevance
“…Cell surface topology of ANT So far, only three studies on Leishmania, murine fibroblasts, and breast carcinoma and fibrosarcoma cells provide solid evidence that ANT is not only localized in mitochondria, but also at the cell surface (Sigal and Resh, 1993;Detke and Elsabrouty, 2008;Radichev et al, 2009). Our study confirms these findings and shows that the three ANT loops that project into the lumen of mitochondria are exposed at the neuronal cell surface (Fig.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Cell surface topology of ANT So far, only three studies on Leishmania, murine fibroblasts, and breast carcinoma and fibrosarcoma cells provide solid evidence that ANT is not only localized in mitochondria, but also at the cell surface (Sigal and Resh, 1993;Detke and Elsabrouty, 2008;Radichev et al, 2009). Our study confirms these findings and shows that the three ANT loops that project into the lumen of mitochondria are exposed at the neuronal cell surface (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Since it has been reported that ANT is located at the plasma membrane of Leishmania, fibroblasts, and cancer cells (Sigal and Resh, 1993;Detke and Elsabrouty, 2008;Radichev et al, 2009), and since we demonstrated that ANT interacts with the extracellular domain of L1, we tested whether ANT1 and/or ANT2 are present at the cell surface of cultured cerebellar neurons. Therefore, live primary cultures of cerebellar neurons were subjected to cell surface biotinylation, and biotinylated proteins were isolated using streptavidin-conjugated beads.…”
Section: Ant Is Present In Plasma Membranes Of Cerebellar Neuronsmentioning
confidence: 99%
“…63 However, at present it is not clear whether Figure 1 Molecules influencing ANT-mediated pore formation in chemically defined systems. The upper part lists proteins affecting the pore function of ANT, whereas the lower part focuses on non-protein molecules.…”
Section: Peripheral Benzodiazepin Receptormentioning
confidence: 99%
“…Crosslinking experiments identified a 32-kDa protein as the major species labeled by a myristoylated amino-terminal Src peptide probe (12,13). However, upon purification, this protein was found to be the ADP/ATP carrier, a mitochondrial protein capable of binding myristoyl-Src peptide but not the Src protein (14). To date no other protein has been identified as a binding partner for the Src amino terminus.…”
mentioning
confidence: 99%